PENGARUH KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA APARATUR PEMERINTAH DAERAH DENGAN PENGENDALIAN AKUNTANSI SEBAGAI VARIABEL MODERASI - Utami, Alvitria; Sarwono, Aris Eddy; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to appreciate the influence of clarity of budget targets andaccounting controls on the performance accountability of local governmentagencies. This research was conducted on the State civil apparatus. SukoharjoRegency. The type of data used is quantitative data. The data source used isprimary data. Data collection techniques for documentation, questionnaires, andliterature study. The population used in this study are all apparatuses who aremembers of the Sukoharjo District OPD. The sample used in this study is the headand employees of the financial department (Treasurer), and employees whoprepare financial statements. The sampling technique was using purposivesampling method. This study shows that the clarity of budget targets andaccounting controls influences the performance accountability of localgovernment agencies.